Proposed upgrading Kinta Golf Club Jalan Changkat 31000 Batu Gajah Perak Malaysia / Amirul Hisam Alias - Alias, Amirul Hisam (Faculty of Architecture, Planning and Surveying, 2012)
This project is mainly about proposed upgrading Kinta Golf Club Jalan Changkat 31000 Batu Gajah Perak Malaysia.The total interior is 19,800 sq.This Golf Club was establish since 1921 almost 100 years and never been upgrade to improve their customer needs and satisfication.The site is located at Batu Gajah Perak.lt is ideally located at strategic area because it is in centre of Batu Gajah which is near all residential,commercial area,recreation park,education, government administration, and near to public transportation.There are several problem in term of design after making research,observation, and further studies about the site itself, and problems with customers flow and staff.This upgarding will solve the problems by rearrange spaces and giving new looks of interior to improve the quality of the business and solving some error on customers and staff flow with new look design